2000
DOI: 10.1023/a:1026477628723
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Both underweight and overweight have negative effects on IVF parameters and outcome leading to decreased chances of pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(36 citation statements)
references
References 17 publications
2
33
1
Order By: Relevance
“…In our study we managed to gather a homogeneous group of 70 BMI<26 PCOS women. By including only non-obese women with PCOS we decreased the risk of possible influence of metabolical disturbances and negative impact of the obesity on the oocyte number and the duration of the stimulation [13,14]. Furthermore, to study LH dynamics during COH in both protocols we decided to exclude BMI inhibitory effect on LH [25,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study we managed to gather a homogeneous group of 70 BMI<26 PCOS women. By including only non-obese women with PCOS we decreased the risk of possible influence of metabolical disturbances and negative impact of the obesity on the oocyte number and the duration of the stimulation [13,14]. Furthermore, to study LH dynamics during COH in both protocols we decided to exclude BMI inhibitory effect on LH [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis by Griesinger et al showed similar benefits of GnRH analogs regarding PCOS populace [11]. On the other hand, meta-analyses mentioned above did not consider high body mass index (BMI) as an exclusion criteria, while current studies report obesity to be associated with relative gonadotropin resistance [12], lower number of collected oocytes [13,14] as well as general poorer IVF outcome [15]. According to the latest consensus on infertility treatment related to PCOS, the optimal stimulation protocol is still under debate [4].…”
Section: Introductionmentioning
confidence: 88%
“…In the last decade, the relationship between body weight, subfertility and inflammatory markers like hs-CRP has been explored in some studies [3,4,24]. White adipose tissue plays a central role in the low grade inflammatory state that is characteristic of obesity [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Increase in maternal age is known to have a negative impact on fertility secondary to reduced ovarian reserve [1,2]. Numerous studies concluded that obesity, as defined by a BMI>25 kg/m 2 negatively correlates with fertility potential, affecting ovulation, pregnancy rates and outcomes in natural and treated cycles [3,4]. There is also evidence that smoking negatively impacts on all areas of fertility from follicle development to fertilization and embryo cleavage.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of oocytes from obese women undergoing in vitro fertilization indicate that abnormal lipid accumulation and oxidative stress are associated with impaired oocyte development [9, 10]. Thus, there is a strong biological plausibility for seeking to improve mitochondrial function for fertility enhancement.…”
Section: Obesity and Impaired Mitochondrial Function Of The Oocytementioning
confidence: 99%